Cultural anthropology of Bronisław Malinowski and reflections on the economic crisis - Szulczewski, Grzegorz (Annales. Etyka w Życiu Gospodarczym, 2019)
The paper revisits two theories from the cultural anthropology. The first theory is by Bronisław Malinowski, and the second one by Karl Homann. Malinowski criticizes economism and moralism. I present further stages of this criticism, with special importance placed on the concept of homo oeconomicus. Malinowski demonstrates how moral norms are implemented in primitive cultures by means of magic, cults, customs and rituals and rites. Malinowski also argues for the significance of cultural institutions in stabilizing the functioning of primitive communities. These institutions sheltered the communities from the kind of crises that are also experienced in the present times, thus, giving the older schools of thought in cultural anthropology their deserving place within the contemporary thought.